Effect of air temperature on human births, preterm births and births associated with maternal hypertension. (12th December 2022) - Blavier, Frédéric; Barbe, Kurt; Faron, Gilles; Doutreloup, Sébastien; Boukerrou, Malik; Fuchs, Florent; Gucciardo, Leonardo
Abstract: Objective: We studied potential effects of outdoor air temperatures or barometric pressure on births, preterm births and births associated with maternal hypertension. Methods: 12, 269 births were retrospectively reviewed in Brussel and 25, 880 in South Reunion Island. National Belgium and French weather reference centers provided outdoor air temperatures and barometric pressures from the nearest weather stations on the corresponding birthdays. Poisson regression models were used to assess if outdoor air temperatures or barometric pressure could be correlated, immediately and several days later, with the number of daily births, preterm births and births associated with hypertension. Results: Outdoor air temperature was significantly correlated to the number of daily births in Brussels. For each additional degree Celsius, overall births increased by 0.4% during the same day. Four days later, overall births increased by 1.8%, preterm births by 2.6% and births associated with hypertension by 5.7%. Similar observations on numbers of daily births were reported in South Reunion Island, without reaching statistical significance ( p = .08). Conclusion: As previously demonstrated in recent studies, increased air temperature leads progressively to higher rates of births and preterm births. An even stronger delayed effect of air temperature was observed on births associated with hypertension. This would be worth further investigating.